Strategy For Improving The Performance of State Civil Service In Developing Employee Performance Targets In The Government Environment of Tanah Bumbu District - Dahliansyah Dahliansyah; Andi Tenri Sompa; M. Riduansah Syafari (Wadah Inovasi Indonesia, 2021)
This study aims to describe the strategy of improving the State Civil Apparatus (SCA) performance in preparing Employee Performance Targets (EPT) within the Tanah Bumbu Regency Government. This research is motivated by the low ability of SCT in the practice of EPT in the Tanah Bumbu Regency Government. Through this research, it is hoped that strategies that have been carried out can be identified, evaluated, and provide recommendations for systems that can be used. The theory used to answer the problem is the theory of employee performance improvement strategies in EPT preparation. This research method uses a qualitative approach with a descriptive research type. The research subject is the Head of Human Resources Agency of Tanah Bumbu Regency. The research locus, namely Human Resources Agency as the best agency in preparing EPT, and the Health Office as the lowest agency to prepare EP. The data collection type is primary and secondary data, and data collection techniques are carried out through interviews, documentation, and observation. This study indicates that the Human Resources Agency applies a strategy to create a harmonious organizational climate and effective leadership. In contrast, the Health Office involves a pleasant organizational environment, effective leadership, and career development. Based on the comparisons made, the Department of Health needs to optimize the strategies that have been carried out. The suggestions that can be given to the Tanah Bumbu Regency Government are to improve the performance of SCT in the preparation of EPT by optimizing the strategy of creating a harmonious organizational climate, maximizing the role of effective leadership, and developing ASN careers